Phytoremediation with Acasia (Acasia crassicarpa) on peat soil using fly ash and dreg as ameliorants - Rejeki, Yayuk Sri; ', Nelvia; ', Saryono (Indonesian Journal of Environmental Science and Technology, 2014)
Utilization of fly ash and dreg on peat soil to improve soil fertility is potential because there are largeamount of fly ash and dreg as well as the existence of critical. This study was aimed to determine the effect of fly ash and dreg on the growth and the accumulation  of metals Ba, Cd, Cr, Ni, Pb, and Se of Acacia crassicarpa and its absorption  efficiency in the peat soil. The results showed that the addition of fly ash and dreg with dif ferent doses and different  harvesting  time influenced  on the growth and the accumulation  of heavy metals in Acacia crassicarpa. The results of the study also indicated that there were differences in the absorption efficien cy of heavy metals by Acacia crassicarpa.Keywords: fly ash, dreg, metal accumulation, absorption efficiency, Acacia crassicarpa.